Associação entre fatores psicossociais do trabalho e a obesidade e dor multirregional em trabalhadores da saúde - Vieira, Ludmilla Maria Souza Mattos de Araújo (2024)
Psychosocial aspects have been studied even before the COVID-19 pandemic and there is concern about healthcare workers as they are exposed to tense situations, with the need to make quick and emotionally exhausting decisions. During this period, workers experienced unfavorable conditions and rapid deterioration of the psychosocial aspects of work, leading to the emergence and worsening of musculoskeletal disorders and obesity. Therefore, this investigation is important and verify whether there is an association between the variables. Objective: To investigate the association between psychosocial aspects with multiregional pain and obesity in healthcare workers. Methods: Cross-sectional study with 344 workers from the HEROES and IMPPAC cohort databases, including healthcare workers who answered the Nordic Musculoskeletal Symptoms Questionnaire and the Copenhagen Psychosocial Questionnaire. Both cohorts were approved by the ethics committee and the participants signed an informed consent form. Data were analyzed using binomial logistic regression and the Body Mass Index (BMI) was calculated from the ratio between body mass (in kg) and height squared (in meters). BMI was dichotomized into obesity (BMI > 30 kg/m2) and non-obesity (BMI < 30 kg/m2). Psychosocial aspects were defined based on the dimensions of the COSOQ-IIBr and dichotomized into no risk for psychosocial aspects if the score was adequate (no risk = 0) and if the score indicated attention or risk, there was risk for psychosocial aspects (with risk = 1). Multiregional pain was defined from the regions with pain in the last 12 months and 7 days, according to the Nordic Musculoskeletal Symptoms Questionnaire, using the SPSS software (version 26.0) and the significance level adopted was 5% (α = 0.05). Results: Most health workers were female (78.5%); 34.6% were overweight and 22.7% were obese. The most critical dimensions of the COPSOQ were emotional demands, burnout and stress, with the proportion of workers in the risk category being 75.6%, 84.0% and 81.7%, respectively. In the logistic regression between psychosocial aspects and obesity, there was a significant association between obesity and predictability (OR=1.85 95%CI 1.09-3.13), recognition (OR=1.94 95%CI 1.10-3.39), trust in management (OR=2.12 95%CI 1.03-4.36), social support (OR=1.83 95%CI 1.03-3.23), work-family conflict (OR=1.70 95%CI 1.00-2.85), health and well-being (OR=2.27 95%CI 1.15-4.49) and burnout (OR=2.45 95%CI 1.04-5.78). In the logistic regression between psychosocial aspects and multiregional pain, there was a significant association between multisite pain and work pace (OR=3.58, 95%CI 1.36-9.43), emotional demands (OR=3.92, 95%CI 1.42-10.8), work-family conflict (OR=3.29, 95%CI 1.20-9.05), burnout (OR=4.17, 95%CI 1.39-12.5) and stress (OR=3.20, 95%CI 1.14-8.99). Conclusions: A significant association was identified between obesity and multiregional pain with several psychosocial aspects, with burnout standing out in both models analyzed. Considering that psychosocial factors play a crucial role in maintaining health, the relationship between these factors, obesity and multiregional pain should be further investigated in prevention programs aimed at psychosocial health. This deepening can contribute to the development of more effective intervention and health promotion strategies.